If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(4/5)*x-3 = x-(1/3) // - x-(1/3)
(4/5)*x-x+1/3-3 = 0
-1/5*x-8/3 = 0 // + 8/3
-1/5*x = 8/3 // : -1/5
x = 8/3/(-1/5)
x = -40/3
x = -40/3
| x+24+4x=-21-4x-27 | | 7y=-7y | | 8(x-3)+6= | | 25+4x^2=-20x | | -26=m/11-8 | | -3r+2r=1 | | -3x=2x+20 | | 42x-81=63-54x | | ab+aw=c-aw | | (a/2)+4=12 | | 4(x+5)=-48 | | -4(p+7)=2(1-p) | | s-9=23 | | 35+(20x)=60+(10x) | | 1/9x-10=70 | | x-3/4=x+6/20 | | 5x+6=-8+3x+20 | | 9n+5-3(n-1)=15 | | 2(8t^2+32t-14)=0 | | 4(3-x)+6x=x+12-3X | | 3.45=x*5+9*5 | | ((1/3)(2x-4))+5=((-2/3)(x+1)) | | y=2/3(1)+4 | | 1/4x-9=6 | | 11x-16=-5x | | 2n-4=9 | | 2b-8+9b-6b= | | 7-4.9t=-15+7.6t | | 14x+6-5x=3 | | 8.50+a=38.45 | | -27=9+4m | | 3+4c=3c+6 |